Efforts to Improve Learning Results in Understanding the Solar System in Science Learning in Class VI SDN Batulawang Through the Use of Audio Visual and Planetarium Drawings - Maman Setiaman (PT FORMOSA CENDEKIA GLOBAL, 2023)
Learning is a process, of course in a process there are interrelated components. The main components in learning include learning objectives, educators, students, curriculum, learning strategies, learning media, and learning evaluation. Solar System Media has a good impact on educators to develop learning techniques so that they can improve learning achievement for the better. The purpose of this study was to improve student achievement using planetarium teaching aids for learning the Solar System in the subject of Natural Science Class VI at SDN Batulawang, Cibalong Tasikmalaya District. So, this research approach uses Classroom Action Research. The instruments used are observation sheets, interviews, and tests. Based on the results of research and action it can be concluded that the use of planetarium teaching aids can improve student learning outcomes. There was an increase in the completeness of student learning outcomes from the initial conditions to cycle II. From the initial conditions, learning completeness was only 40.62%, increasing to 71.87% in cycle I and to 96.875% in cycle II. Student learning outcomes in the form of the highest and lowest scores also increased.